Gain enhancement and side lobe level reduction of array LTCC antenna for radar application / Mohd Hisyamuddin Mat Yusoof - Mat Yusoof, Mohd Hisyamuddin (2013)
A 2x2 Array Low Temperature Co-fired Ceramic (LTCC) Antenna with Metal Ring operating at 9.41GHz for Radar Application is presents in this paper. Metal ring has been used integrated with aperture coupled feeding method and rectangular patch radiating element to enhance the antenna performance. LTCC of 8 layers substrate offers high dielectric constant, Er = 5.9 and 96μm thickness by using Ferro A6S, while silver metal thickness is lOμm. Simulations of the LTCC antennas were done Qy using CST Microwave Studio Software. The results of return loss (S11), voltage standing wave ratio (VSWR), bandwidth (BW), half power beam width (HPBW), Side Lobe Level (SLL) and gain are compared and analysed between the Single Patch, 1 x2 and 2x2 Array LTCC antennas. All the results show good performances of the designed LTCC antennas and well matched at the input. The 2x2 array LTCC antenna with metal ring was able to reduce the side lobe level to -22.lOdB (39% reduction) and enhanced gain to 9.68dB (42% increment) as compared to the single LTCC antenna with metal ring.